LOS CRISTIANOS DE IRAK EN PELIGRO DE DESAPARECER - Rufail, Emilio Alejandro (Centro de Estudios Avanzados, 2018)
USA invasion to Iraq in 2003 was the cause of the fall of SaddamHussein´s regime and it gave rise to the violence of sects which in turnaffects the whole Iraqi society.Apart from the violent struggles for power between the Shiite andSunite Islamic groups, little is known about the violence they inflictedupon Christian communities. Christians have been living in that regionfor over two thousand years before the region was islamized. Thesecommunities have great diversity and are made up of differentchurches ; their members belong to different ethnias but they all sharethe impact of being victims of a genocide process on the side of radicalIslamic groups which intend to homogenize Iraq in the Islam withoutany room left for the Christians.This article resorts to a theoretical tool called «periodization of agenocide process» and it is very useful at the time of identifying,describing and analyzing the steps which are part of a genocide process.The presence of Christians in Iraq has remarkably decreased due tothreats, kidnappings and murders and the situation has worsenedbecause of the tendency of aggressors to consider Christians as alliesof the invaders and collaborators of Saadam´s regime ; under thesecircumstances they are, of course, the most common sterotypes andconsequently responsible for the evil that affects Iraq.